Umbilical cord constriction as a cause of intrauterine fetal death - Victor Antônio Kuiava; Henrique M. Pasqual; Ana Luiza S. Garcia; Bianca L. Barbarioli; Fernanda M. Carlotto; Gabriel K. Costa; Laurenlisiê L. H. Brittes; Maiara Christine Macagnan; Nathália Dal Prá Zucco; Rubens Rodriguez
ABSTRACT The umbilical cord constriction (UCC) is an uncommon condition and an important etiology for stillborn fetuses. The main goal of this study was to verify the UCC occurrence as the cause of intrauterine fetal death, the associated etiology and its pathological characteristics. Therefore, a descriptive retrospective cross-sectional study was developed using the database from a Pathology Institute, in Brazil, from 1995 to 2017. The results presented a total of 1,359 embryo/fetus deaths - 69 (5.07%) due to UCC, 60.9% males and 39.1% females. The average age of pregnant women was 27.5 years ± 7.2 years of standard deviation (SD). The majority of deaths occurred during the second trimester (76.5%), followed by the first (14.7%) and third (8.8%) trimesters, respectively. One constriction alone was found in 87% of cases, 11% had two constrictions and only 1% had three or more. The presence of congenital malformations was detected in 20.2% of necropsies, the identification of chronic fetal distress was described in 71% of the technical reports and 17% of the cases had obstructive vasculopathy characteristics in microscopy analysis. Regarding the anatomopathological characteristics between the male and female sexes, no significant difference was found (p > 0.05) correlating gestational age, weight or congenital malformations. UCC was a cause of fetal death found in 5% of the cases, and it was linked to congenital malformations, fetal distress and obliterative vasculopathy.